New acylated anthocyanins from purple yam and their antioxidant activity. Issue 9 (2nd September 2015) - Moriya, Chiemi; Hosoya, Takahiro; Agawa, Sayuri; Sugiyama, Yasumasa; Kozone, Ikuko; Shin-ya, Kazuo; Terahara, Norihiko; Kumazawa, Shigenori
Abstract: Purple yam ( Dioscorea alata L.), which is widely distributed in tropical and subtropical regions, is characterized by its color and viscosity. Previous studies have shown that purple yams contain a variety of acylated anthocyanins that exhibit higher levels of antioxidant activity than the corresponding nonacylated compounds. In this study, the pigments found in purple yams from the Philippines ( D. alata ) were isolated and evaluated in terms of antioxidant activity. Four new acylated anthocyanins, alanins (1 –4 ) were isolated from the MeOH extracts of purple yam, which were subsequently determined to be cyanidin (1, 2, and 4 ) and peonidin (3 ) type compounds, along with four known anthocyanins (5 –8 ). The structures of 1 –4 were determined by spectroscopic methods, including NMR and MS analyses. The antioxidant activities of anthocyanins 1 –8 were investigated using oxygen radical absorbing capacity and ferric reducing antioxidant power assays. Graphical abstract: : alatanins D-G, acylated anthocyanins, were newly isolated from purple yam from the Philippines. These structures were determined and the antioxidant activities were evaluated.